Visual techniques for categorical data in R - Brzezińska, Justyna (Metody wizualizacji danych w programie R, 2017)
Visualization is one of the most important parts of statistical analysis. In this paper we present a new method of multiple bar charts to display the frequencies of data tables split up into conditional relative frequencies of one target variable and the absolute frequencies of the corresponding combinations of the remaining explanatory variables. In this paper we present the R package extracat allowing for new graphical tools: rmp and cpcp plot [Pilhoefer, Unwin 2013]. The first plot uses the a crossover of mosaicplots and multiple barcharts to display the frequencies of a contingency table split up into conditional relative frequencies of one target variable and the absolute frequencies of the corresponding combination of the remaining explanatory variables. It provides a well-structured representation of the data with the possibility of easy interpretation. Another plot presented in the paper is the cpcp plot using parallel coordinates. Sequences of points are used to represent each of the variable categories, while ordering algorithms are applied to represent a hierarchical structure in the dataset
Ekonometria = Econometrics, 2017, Nr 3 (57), s. 26-36
Keywords: visualization; categorical data; multiple bar charts; R software; wizualizacja; dane jakościowe; wielowymiarowy wykres słupkowy; program R